2010
DOI: 10.1007/s10822-010-9323-y
|View full text |Cite
|
Sign up to set email alerts
|

3D-Pharmacophore mapping of thymidine-based inhibitors of TMPK as potential antituberculosis agents

Abstract: Tuberculosis (TB) is the primary cause of mortality among infectious diseases. Mycobacterium tuberculosis monophosphate kinase (TMPKmt) is essential to DNA replication. Thus, this enzyme represents a promising target for developing new drugs against TB. In the present study, the receptor-independent, RI, 4D-QSAR method has been used to develop QSAR models and corresponding 3D-pharmacophores for a set of 81 thymidine analogues, and two corresponding subsets, reported as inhibitors of TMPKmt. The resulting optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Several of these studies have either suggested compounds for testing that have been validated or in several cases this validation is yet to be achieved. These hybrid methods can confirm the pharmacophore or QSAR model, with recent examples including thymidine analogs as inhibitors of thymidine monophosphate kinase (TMPK) [41]. Furthermore, in a search for InhA inhibitors, a 3D-QSAR-derived pharmacophore model was used to narrow down a set of 230,000 compounds to 299 top-scoring hits and ultimately 30 whose lowest energy docked conformation showed significant interactions with key active site residues, i.e.…”
Section: Computational Cheminformatic Tools and Their Usesmentioning
confidence: 99%
“…Several of these studies have either suggested compounds for testing that have been validated or in several cases this validation is yet to be achieved. These hybrid methods can confirm the pharmacophore or QSAR model, with recent examples including thymidine analogs as inhibitors of thymidine monophosphate kinase (TMPK) [41]. Furthermore, in a search for InhA inhibitors, a 3D-QSAR-derived pharmacophore model was used to narrow down a set of 230,000 compounds to 299 top-scoring hits and ultimately 30 whose lowest energy docked conformation showed significant interactions with key active site residues, i.e.…”
Section: Computational Cheminformatic Tools and Their Usesmentioning
confidence: 99%
“…Due to all the aforementioned factors, we expect a shift in the QSAR role. QSAR would move from being applied to lead optimization processes toward a role as a tool integrating early stages of computeraided drug design and experimental drug-discovery pipelines [19,20]. However, there are still challenges to be overcome, such as the implementation of robust validation processes and automation of different parts involved in the generation of predictive QSAR models.…”
Section: Future Perspective In New Technologies and Large-scale Qsarmentioning
confidence: 99%
“…The 3D‐pharmacophore maps were then used to design structural changes on the TMPKmt inhibitors and to predict anti‐TMPKmt activity for novel and more potent compounds. Finally, the receptor‐independent 4D‐QSAR models provided insights about the possible mechanism of action of the TMPKmt inhibitors …”
Section: Experimental Strategies Commonly Used To Find New Anti‐tb Drugsmentioning
confidence: 99%